Clarifying the Dominant Logic Construct by Disentangling and Reassembling its Dimensions. (10th May 2020) - Engelmann, Alexander; Kump, Barbara; Schweiger, Christina
Abstract: Since its introduction, Prahalad and Bettis's concept of dominant logic has informed a variety of scholarly conversations in management and strategy research. However, scholars have interpreted dominant logic in different ways, emphasizing different aspects, such as managerial mindsets, administrative tools and management functions, as defining elements. Similarly, empirical studies have captured various aspects, such as meanings of entrepreneurs, observable strategic decisions and business model similarity, as indicators of dominant logic. Consequently, the concept lacks analytical clarity, and it is difficult to compare or generalize findings from this diverse set of studies. The aim of this review is to improve conceptual clarity by analysing, comparing and evaluating the existing interpretations and assessments of dominant logic in 94 studies. In the first part of the review, by disentangling the interpretations of the concept, we show that dominant logic consists of four defining dimensions: (i) shared mental models; (ii) values and premises; (iii) organizational practices; and (iv) organizing structures. In the second part, we reassemble dominant logic into an integrative model and theorize about how these dimensions operate in concert to produce a firm's dominant logic. Thus, our main contribution is a clarification and synthesis of the literature, which comes with implications on how future research can conceptualize and operationalize dominant logic more consistently.